Mutual trade between ASEAN and China - Sadovskaia, Mariana; Bolotov, Ilya; Shymanska, Kateryna; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
The aim of this thesis is to examine ASEAN–China economic cooperation mainly from the ASEAN perspective and assess how regional integration has influenced bilateral trade ties between China and ASEAN member states from 2010–2022. The research question is whether there is potential for further development of this economic partnership given the ASEAN member countries' bilateral trade relations with China. The thesis provides a comprehensive analysis of the evolution of economic integration between ASEAN and China, examining major agreements and initiatives such as the ASEAN-China Free Trade Agreement (ACFTA) and the Belt and Road Initiative (BRI). The study investigates the macroeconomic performance, trade in goods, investment flows, and bilateral trade ties between selected ASEAN member states and China. The findings indicate significant growth and strengthening of trade ties, with China becoming ASEAN's largest trading partner. However, trade imbalances and geopolitical tensions, particularly over the South China Sea disputes, pose challenges. While there is substantial potential for deepening economic partnerships, ASEAN members must navigate this process carefully to optimize gains while mitigating risks.
Vedoucí práce: Ilya Bolotov
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor bakal. práce]; bakalářské práce; bachelor's theses